2015
DOI: 10.1016/j.jconrel.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol (PEG)-dendron phospholipids as innovative constructs for the preparation of super stealth liposomes for anticancer therapy

Abstract: Pegylation of nanoparticles has been widely implemented in the field of drug delivery to prevent macrophage clearance and increase drug accumulation at a target site. However, the shielding effect of polyethylene glycol (PEG) is usually incomplete and transient, due to loss of nanoparticle integrity upon systemic injection. Here, we have synthesized unique PEG-dendron-phospholipid constructs that form super stealth liposomes (SSLs). A β-glutamic acid dendron anchor was used to attach a PEG chain to several dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 46 publications
5
117
0
1
Order By: Relevance
“…Pasut et al (2003) described new PEG-dendron-phospholipid constructs that they assembled into structures called super stealth liposomes (SSLs). This was achieved by using a b-glutamic acid dendron to anchor a PEG chain to distearoyl phosphoethanolamine lipids.…”
Section: Improving Circulation Time: Stealth Liposomesmentioning
confidence: 99%
“…Pasut et al (2003) described new PEG-dendron-phospholipid constructs that they assembled into structures called super stealth liposomes (SSLs). This was achieved by using a b-glutamic acid dendron to anchor a PEG chain to distearoyl phosphoethanolamine lipids.…”
Section: Improving Circulation Time: Stealth Liposomesmentioning
confidence: 99%
“…In vitro studies suggested that SSLs have low toxicity and high intracellular uptake. In addition, cell culture studies have also demonstrated that doxorubicin loaded in SSLs outperformed doxorubicin formulated in classic stealth liposomes as well as in free doxorubicin [95]. …”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…At times, PEG's shielding effect is incomplete and transient due to the loss of liposome integrity after systemic injection. As a consequence, our group and colleagues set out to synthesize unique PEG-dendron-phospholipid constructs with an increased number of phospholipids per polymer chain [95]. PEG shielding is generally achieved by using PEG-monophospholipid derivatives, such as methoxy-PEG-distearoyl phosphoethanolamine (mPEG-DSPE).…”
Section: Pegylated Liposomesmentioning
confidence: 99%
“…In fact, a substantial amount of systemically injected particles typically accumulate in these organs due to immunological clearance [47]. Traditionally, stealth polymers, such as PEG, have been used to reduce particle opsonization, thereby decreasing macrophage uptake and prolonging blood circulation times [102-104]. Nevertheless, repeated injections of pegylated nanoparticles can give rise to the formation of antibodies against PEG, thereby resulting in accelerated clearance of these particles [105].…”
Section: Geometrical Molecular and Biomimetic Targeting Strategiesmentioning
confidence: 99%